The study on the end-user satisfaction towards the utilisation of myshelves as teaching and learning aid: From the perspective of UiTM Johor / Suhaila Osman...[et al.] - Osman, Suhaila; Wahi Anuar, Muhammad Asyraf; Ahmad, Rohayu (Universiti Teknologi MARA, Kedah, 2018)
With the evolution of technology nowadays, the learning process has changed. The use of technology gives a big impact towards the transformation of education. Almost all universities have their own Learning Management System (LMS) but unfortunately, some are not properly maintained. Universiti Teknologi MARA (UiTM) has its own LMS but there are some obstacles faced by the users in accessing it. Therefore, a new mechanism needs to be developed in order to support the learning process. This study proposes a new system in learning, known as MySHELVES. Hence, this study was undertaken to determine the effectiveness of and the end-user satisfaction towards the usage of MySHELVES in the learning development process. Some models were used by other studies conducted by a range of authors from different perspectives. However, the researchers in this study used a model by Doll and Torkzadeh (1988) known as the End User Computing Satisfaction (EUCS). ALthough this model consists of 12 instruments, only 5 were selected based on the suitability of this study. A set of a questionnaire was used for data collection and the students from UiTM this study. Specifically, the research was conducted in UiTM Johor and focused on the Diploma students from the Faculty of Information Management. This study used Simple Random Sampling as the sampling design. Only 100 respondents were selected and the questionnaires were subsequently distributed to them. Findings show that the respondents were satisfied with the usage of MySHELVES in their learning process. The author recommends the utilisation of MySHELVES by other faculties in UiTM so that the new mechanisms could assist the learning process to be more interactive.